Strategi Pembelajaran Berbasis Masalah dalam Meningkatkan Kemampuan Problem Solving Peserta Didik - Sri Wati Putri; Adillah Almufidah; Gusmaneli Gusmaneli (CV. Aksara Global, 2024)
This research aims to improve and develop students' abilities to learn how to think critically in finding solutions to problems. Based learning strategy is a learning strategy that invites students to learn independently, carry out discussions, find solutions to solve problems and be able to draw conclusions. This research aims to examine more deeply problem-based learning strategies so that students can develop their abilities to overcome complex and diverse problems. The data collection used by researchers is a literature study by studying and citing several sources from textbooks, articles, journals, modules and other publications. The use of this learning strategy is expected to improve students' problem solving abilities.